IMPROVING STUDENTS’ ENGLISH VOCABULARY MASTERY THROUGH PICTIONARY GAME OF SD NEGERI 22 RUMBIO - Wida Rianti (Journal of English Language and Education, 2018)
This study discussed about using Pictionary game to improve students’ vocabulary mastery to the third grade students of SDN 022 Rumbio. The data were gathered from classroom observations and interview. The analysis showed how Pictionary game gave an improvement in pronouncing, knowing and memorizing words. It provided opportunities for students to improve the vocabulary mastery as well as motivation to help the teacher managing classroom interaction. It also enabled the students to experience the vocabulary; they made noticeable progress in their vocabulary learning, gaining the confidence to pronounce word in pronouncing. In short, this study showed that Pictionary game promoted students active participation in the activities with more opportunities to improve their vocabulary through practice which in turn increased their positive attitude for language learning.